Comparison of Analgesic Effects of Nalbuphine and Buprenorphine on Caudal Ropivacaine in Children Undergoing Infraumbilical Surgeries - Kaur, Navdeep; Chinnappa, Jithendra; Suresh, Govindswamy; Turai, Ashwini; Iyer, Sadasivan Shankar (Journal of Anaesthesia and Pain, 2025)
Background: Caudal anesthesia is the most commonly performed regional anesthesia in children. Nalbuphine and buprenorphine provide the advantage of prolonging the duration and quality of analgesia without the risk of respiratory depression. The study compares the analgesic effects of nalbuphine versus buprenorphine on caudal ropivacaine. Method: Randomized, double-blind study on 54 patients aged 1-10 years scheduled for elective infraumbilical surgeries, randomly assigned to three groups. Group R (n = 17, receive ropivacaine 0.2% 1 ml/kg), group RN (n = 17, receive 0.2% ropivacaine with 0.1 mg/kg nalbuphine), and group RB (n = 17, receive 0.2% ropivacaine with 3 µg/kg buprenorphine). The time taken for the first rescue analgesic, children and infants postoperative pain scale (CHIPPS), sedation scores, motor blockade, and side effects were noted every 30 minutes in the postoperative room. Data were analyzed using students’ unpaired t-test, ANOVA, Yates' and Fisher’s chi-square tests, with α = 0.05 and 95% confidence intervals (CI). Result: Time to rescue analgesia was 15.54 ± 7.74 hours in RN, 17.96  ±  5.56 hours in RB, and 11.25  ± 8.85 hours in R group. Most patients had a CHIPPS score of 1 in all 3 groups. Motor blockade was not present in all groups (p = 0.650). All three groups were comparable in sedation scores (2, tranquil and oriented) (p = 0.650). There were no significant difference in the side effects between groups (p = 0.060).     Conclusion: Both nalbuphine and buprenorphine prolong the duration of postoperative analgesia when combined with caudal ropivacaine, compared to solely caudal ropivacaine.